DOI: 10.18297/etd/2217
|View full text |Cite
|
Sign up to set email alerts
|

Suramin protects from cisplatin-induced acute kidney injury.

Abstract: In rodent models, suramin improves recovery following acute kidney injury (AKI). We hypothesized that suramin would be useful in protection against cisplatin-induced AKI.This hypothesis was tested by pre-treating C57BL/6j mice with suramin prior to cisplatin.Our data indicates that suramin protects the kidney from injury by decreasing cisplatininduced decreases in kidney function. Renal histology indicated that suramin significantly protected from cisplatin-induced AKI. Data indicate that suramin pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Therefore, it is still necessary to identify novel effective strategies to minimize the renal cytotoxicity of CDDP. Of all these approaches used, natural compounds have been shown to provide promising protection [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is still necessary to identify novel effective strategies to minimize the renal cytotoxicity of CDDP. Of all these approaches used, natural compounds have been shown to provide promising protection [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Injury and death of renal tubular epithelial cells are characteristics of AKI induced by ischemia/reperfusion (I/ R). Epithelial cells in the proximal tubule are commonly affected when ischemia occurs in the kidney [17]. Characteristic changes in histology in tubular cells include dilatation of the tubular lumen, loss or effacement of the tubular brush border, and formation of casts because of apoptosis [18].…”
Section: Cg 4hmentioning
confidence: 99%
“…Studies have demonstrated that the inhibition of overexpression of CHOP can decrease cell apoptosis and alleviate AKI. For example, when cisplatin was administered to mice to develop an AKI model, AKI was associated with activation of ERS, and kidney function increased and renal cell apoptosis decreased with the inhibition of expression of CHOP [17]. In another animal experiment, tunicamycin, a type of antibiotic, is known to lead to ERS and is used to induce AKI.…”
Section: Cg 4hmentioning
confidence: 99%
“…Approximately one-third of patients treated with cisplatin suffered from renal dysfunction and injury, especially acute kidney injury (AKI), which has become the most di cult problem in the application of cisplatin [3]. Unfortunately, there is currently no effective treatment to prevent cisplatin-induced AKI [4].…”
Section: Introductionmentioning
confidence: 99%